Deepfake-Driven Social Engineering: Threats, Detection Techniques, and Defensive Strategies in Corporate Environments - Kristoffer Torngaard Pedersen; Lauritz Pepke; Tobias Stærmose; Maria Papaioannou; Gaurav Choudhary; Nicola Dragoni (Journal of Cybersecurity and Privacy)
The evolution of deepfake technology has the potential to reshape the threat landscape in corporate environments by enabling highly convincing digital impersonations. In this paper, we explore how artificial media produced by AI can be misused to assume authoritative personas, leaving traditional cybersecurity programs with significant vulnerabilities. Drawing from interviews with cybersecurity professionals across various industries, we find that the majority of organizations remain vulnerable due to their adoption of broad, vendor-centric security solutions that are not specifically designed to protect against deepfake attacks. In response to the evolving threat landscape, we introduce the PREDICT framework—a cyclical, iterative theoretical model. This model combines definitive policy direction, organizational preparedness, targeted employee training, and advanced AI detection tools. Additionally, it incorporates effective incident response plans with continuous improvement and simulations. Our findings underscore the need to revise the current security protocols and offer practical suggestions for strengthening corporate defenses against the increasingly dynamic threat landscape posed by deepfakes.